Financial literacy of secondary school teachers in the Department of Education–Division of La Union - Paneda, Mary Grace P.; Albay, Eduard M. (Institute of Advanced Engineering and Science, 2025)
Understanding the financial literacy of public secondary teachers is vital in promoting financial well-being for both educators and students. Using an adapted questionnaire as the main data-gathering tool, this descriptive study investigated the extent of financial literacy of public secondary teachers from a municipality in the Philippines across various aspects like knowledge, management, credit, savings, investments, and challenges they encountered. The results revealed that teachers often face difficulties and constraints with financial management, budgeting, and investing. The teachers indicated a low level of financial literacy due to their limited understanding of and ineffective strategies in utilizing various financial skills and concepts.